The Draft Genome Sequence of Corynebacterium diphtheriae bv. mitis NCTC 3529 Reveals Significant Diversity between the Primary Disease-Causing Biovars - Sangal, Vartul (American Society for Microbiology, 2012)
We report the draft genome of the human pathogen Corynebacterium diphtheriae bv. mitis NCTC 3529. This is the first C. diphtheriae bv. mitis strain to be sequenced and reveals significant differences from the other primary biovar, C. diphtheriae bv. gravis.